1985
DOI: 10.1161/01.hyp.7.4.578
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of body fat and fat pattern to blood pressure level.

Abstract: SUMMARY Although the association between body weight and blood pressure is irrefutable, body fat mass and blood pressure level may not necessarily be directly related. To clarify the relative contribution of fat mass to blood pressure level, we analyzed data on 399 adults consecutively entering a weight control program. Although most subjects were notably overweight (mean ideal body weight 177%), the population represented a wide spectrum of body weights and blood pressure levels. Study parameters included bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(53 citation statements)
references
References 36 publications
2
49
2
Order By: Relevance
“…21 A weaker correlation has been observed between brachial systolic blood pressure and the fat distribution in obese and non-obese subjects. 7,21,31,32 In the present study, we found that the degree of abdominal fat deposition was strongly associated with the decrease in ABI ratio. The validity of this relationship was based on two important findings: (i) the ABI ratio was no significantly correlated with body weight or body mass index, and (ii) the observed correlation did not result from a significant correlation between the WHR and brachial systolic blood pressure but rather from a negative correlation between the WHR and ankle systolic blood pressure.…”
Section: The Abi Ratio and Plasma Insulinsupporting
confidence: 62%
“…21 A weaker correlation has been observed between brachial systolic blood pressure and the fat distribution in obese and non-obese subjects. 7,21,31,32 In the present study, we found that the degree of abdominal fat deposition was strongly associated with the decrease in ABI ratio. The validity of this relationship was based on two important findings: (i) the ABI ratio was no significantly correlated with body weight or body mass index, and (ii) the observed correlation did not result from a significant correlation between the WHR and brachial systolic blood pressure but rather from a negative correlation between the WHR and ankle systolic blood pressure.…”
Section: The Abi Ratio and Plasma Insulinsupporting
confidence: 62%
“…It has been reported that lean body of coronary heart disease ris k factors in subjects with high k factor levels and the morbidity and low waist/ hip ratios (mean ± mass contributes significantly to mean arterial blood pressure, but not to central fat pattern (Weinsier et al 1985). It has also been reported that no significant difference was found between HDL-cholesterol levels in abdominal obese patients and the other type of obese patients (Fujioka et al 1987).…”
Section: Resultsmentioning
confidence: 99%
“…15161836 Only recently have subcategories of obesity, based on the anatomic location of fat deposition, been investigated as stroke risk factors. Body fat deposited on the trunk (central fat deposition), versus the periphery, has been found to be associated with stroke, as well as myocardial infarction, 12 hypertension, 37 and plasma lipid concentrations, 38 in women. Central fat deposition has also been found to be associated with exacerbated coronary artery atherosclerosis, as well as cardiovascular risk factors, in female cynomolgus monkeys.…”
mentioning
confidence: 99%